Pengaruh Piutang dan Simpanan terhadap Sisa Hasil Usaha Koperasi: A Systematic Literature Review Menggunakan Pendekatan PRISMA 2020 dan Pengembangan Model Konseptual Jumlah Anggota sebagai Variabel Moderasi - Nasrullah Nasrullah; Suryani Suryani; Nihayatul Maskuroh; Zaini Ibrahim (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Research on the determinants of Cooperative Net Surplus (Sisa Hasil Usaha/SHU) has grown considerably; however, previous empirical findings remain inconsistent, particularly regarding the effect of receivables on SHU. Moreover, most studies focus solely on direct relationships among financial variables without considering cooperative institutional characteristics that may influence these relationships. This study aims to synthesize empirical Evidence on the effects of receivables and member savings on cooperative SHU while identifying the potential role of the number of members as a moderating variable. The study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. The literature selection process consisted of identification, screening, eligibility assessment, and inclusion stages, resulting in 15 eligible studies. Data were analyzed using thematic synthesis, quality assessment, risk of bias assessment, and Evidence mapping. The findings indicate that member savings consistently exert a positive influence on SHU by strengthening internal capital and enhancing business capacity. In contrast, the effect of receivables on SHU remains inconsistent and is influenced by receivables management effectiveness, financing quality, and cooperative characteristics. The review also reveals that previous studies have rarely examined moderating effects, limiting their ability to explain inconsistent empirical findings. Therefore, this study proposes the number of members as a moderating variable, which conceptually strengthens the relationship between receivables, member savings, and SHU. These findings contribute to the development of Cooperative Theory and provide a conceptual foundation for future empirical research in developing a more comprehensive model of cooperative performance.